A Case Report on Parvovirus B19 Associated Myositis - Nathan D. Oliver; Auleen Millar; Adrian Pendleton (Case Reports in Rheumatology)
Introduction. Whilst there are reports of viral myopathies affecting children and the immunocompromised, infective myositis is a relatively rare inflammatory myopathy in adults. The clinical spectrum can range from benign myalgias to more serious complications in certain risk groups. Case Presentation. We present two cases of myositis as a result of parvovirus B19 infection. Conclusion. Viral myositis and parvovirus B19 associated myositis should be considered in adults presenting with significant myalgia.